Search for the Higgs Boson in H→WW(*) decays in pp̄ collisions at s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Society (APS), 2006)
We present a search for the standard model Higgs boson in H→WW(*) decays with e+e-, e±μ, and μ+μ- final states in pp̄ collisions at a center-of-mass energy of s=1.96TeV. The data, collected from April 2002 to June 2004 with the D0 detector, correspond to an integrated luminosity of 300-325pb-1, depending on the final state. The number of events observed is consistent with the expectation from backgrounds. Limits from the combination of all three channels on the Higgs boson production cross section times branching ratio σ×BR(H→WW(*)) are presented. © 2006 The American Physical Society.